(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The customers have several options to carry out their banking transactions. They can either go to branch to carry out their transactions, use their ATM debit card, use their credit card or internet banking, mobile banking etc. This study aimed to study the impact of demographic variables of the customers on their choice of different modes of banking transactions and also their preferred mode of transaction. For this purpose a questionnaire was developed and distributed to 400 customers from private banks in Cuttack, Bhubaneswar and Rourkela out of which 291 were completed and returned yielding a response rate of 72.8%. In this research the impact of four demographic variables was studied, they are gender, age, occupation and income. The modes of banking transactions which were selected in this study are branch, ATM card, credit card, internet banking and mobile banking. The responses obtained were analysed using t-test and one way ANOVA. In this study it is observed that in case of demographic variable ‘gender’ it was only in case of usage of credit card for bank transaction where there is no significant difference regarding the opinions of male and female respondents. In the case of the demographic variable ‘occupation’ it was only in case of ATM card transactions, there is no significant difference regarding the opinions of the respondents from various occupational backgrounds. ATM was found to be the most preferred mode of banking transaction by the respondents so the intervention of bank employees are required so that the transaction through other modes like internet banking, credit card and mobile banking could be increased.